2018
DOI: 10.1155/2018/6845985
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended Spectrum Betalactamase (ESBL) and Metallobetalactamase (MBL) ProducingPseudomonas aeruginosaandAcinetobacter baumanniiIsolated from Various Clinical Samples

Abstract: This study was conducted with an objective to find the prevalence of extended spectrum betalactamase (ESBL) and metallobetalactamase (MBL) in P. aeruginosa and A. baumannii isolates obtained from various clinical samples. It was conducted in the Department of Microbiology, Adesh Institute of Medical Sciences and Research, Bathinda, over a period of two years from July 2014 to June 2016. Clinical specimens including urine, pus, blood, high vaginal swabs, respiratory samples, and various body fluids were process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 15 publications
10
33
4
Order By: Relevance
“…The positive rate was 51.6%, higher than the rate of 21.8% and 37.5% reported in other studies. 13 In the present study, there were five IMP-positive strains (15.5%) and four VIM-positive strains (12.5%), similar to the results reported previously. 14,15 However, 27 strains were SIM-positive (84.4%), which was the most prevalent MBL gene in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The positive rate was 51.6%, higher than the rate of 21.8% and 37.5% reported in other studies. 13 In the present study, there were five IMP-positive strains (15.5%) and four VIM-positive strains (12.5%), similar to the results reported previously. 14,15 However, 27 strains were SIM-positive (84.4%), which was the most prevalent MBL gene in our study.…”
Section: Discussionsupporting
confidence: 92%
“…20 There is a high prevalence of beta lactamases an metallobetalactamases production from the isolates of P. aeruginosa and A. baumanni in different samples. 21 Kaur et al 2017 reported that the mortality rate of the blood stream infection due to colistin resistance in Klebsiella pneumoniae is 69.3% in a group of Indian patients. 22 A prospective study conducted in the intensive care units of Delhi reported that the neonatal sepsis caused by Acinetobacter baumanii and Klebsiella pneumonia and the bacterial strains were multi drug resistant.…”
Section: Emerging Trends In Antimicrobial Resistancementioning
confidence: 99%
“…On the other hand, third generation cephalosporins (3GCs) have been prescribed to treat quinolone‐resistant bacteria despite low cephalosporin‐susceptibility rate . In India, 25%–89% quinolone resistance and 36%–96% 3GCs resistance has been reported among Enterobacteriaceae in different parts of the country . Thus, quinolone and cephalosporin drugs might not be a good treatment option for pathogenic ESBL‐QR Enterobacteriaceae .…”
Section: Introductionmentioning
confidence: 99%